2018
DOI: 10.1172/jci98931
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α in the uterine stroma permits embryo invasion and luminal epithelium detachment

Abstract: Although it has been reported that hypoxia inducible factor 2 α (Hif2a), a major transcriptional factor inducible by low oxygen tension, is expressed in the mouse uterus during embryo implantation, its role in pregnancy outcomes remains unclear. This study aimed to clarify functions of uterine HIF using transgenic mouse models. Mice with deletion of Hif2a in the whole uterus (Hif2a-uKO mice) showed infertility due to implantation failure. Supplementation with progesterone (P4) and leukemia inhibitory factor (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 68 publications
4
86
0
Order By: Relevance
“…In mice, uterine HIF2α expression is intense during peri‐implantation period . We recently revealed that entire uterine deletion of HIF2α results in implantation failure due to embryo invasion failure in mice (Figure ). Supplementation of both P 4 and LIF does not rescue embryo invasion but recovers decidual growth arrest and inappropriate location of implantation site in uterine HIF2α knockout mice.…”
Section: Embryo Invasion Is Regulated By Hif2α In the Stromamentioning
confidence: 97%
See 4 more Smart Citations
“…In mice, uterine HIF2α expression is intense during peri‐implantation period . We recently revealed that entire uterine deletion of HIF2α results in implantation failure due to embryo invasion failure in mice (Figure ). Supplementation of both P 4 and LIF does not rescue embryo invasion but recovers decidual growth arrest and inappropriate location of implantation site in uterine HIF2α knockout mice.…”
Section: Embryo Invasion Is Regulated By Hif2α In the Stromamentioning
confidence: 97%
“…On day 5 evening, trophoblast cells enter the stromal layer of the endometrium. Thus, embryo implantation is completed …”
Section: Hormonal Control Of Embryo Implantation In Micementioning
confidence: 99%
See 3 more Smart Citations